Is being care-full enough? Reflections on possible impediments to care and student well-being in an academic literacy module - Bharuthram, S.; van Heerden, M. (South African Journal of Higher Education, 2025)
The well-being of students in higher education has become a major concern. This is especially so for first-year students who have to transition into university studies. As such, in our attempt to facilitate a smoother transition into university studies and to enhance student well-being post the Covid-19 pandemic we revised our first-year acadmic literacy module using the lens of care to foster a more responsive and engaging environment. Despite this, student voices from questionnaires, informal conversations and student course evaluations revealed their continued struggles to adjust to university studies. On reflection, we found that some factors may act as possible impediments to care, which may impact student well-being. This contextual article discusses these impediments which we argue are sub-optimal conditions for care-giving and care-receiving. Some implications for research are also considered.